Analisis Pengaruh Upah Minimum Provinsi, Pengangguran, dan Pendapatan Asli Daerah terhadap Penyerapan Tenaga Kerja di Provinsi Sumatera Utara pada Tahun 2001-2022 - Tarigan, Inda Serfina; Hutagalung, Josua Fransesco; Purba, Kristin Yenita; Hidayat, Nasrullah (As-Syirkah: Islamic Economic & Financial Journal, 2024)
This research aims to determine and analyze the influence of the Provincial Minimum Wage, Unemployment, and Original Regional Income on Labor Absorption in North Sumatra in 2001-2022. This research uses quantitative research with the Multiple Linear Regression method, and the type of data used is time series data which is processed with the help of software as an analysis tool, namely Eviews-10. The results of the analysis in this research are that the Provincial Minimum Wage variable has a positive and significant effect on Labor Absorption in North Sumatra Province, and the Unemployment variable in this study has a negative and significant effect on Labor Absorption in North Sumatra Province, and on the Regional Original Income variable which used in this research has a negative but not significant influence on Labor Absorption in North Sumatra Province, where simultaneously there is an influence of the three variables on Labor Absorption in North Sumatra Province.